2015
DOI: 10.1021/acs.joc.5b01109
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Spiroligomer-Containing Macrocycles

Abstract: We demonstrate the synthesis and characterization of the solution conformations of a collection of functionalized spiroligomer-based macrocycles. These macrocycles contain 14 independently controllable stereocenters and four independently controllable functional groups on a highly preorganized scaffold. These molecules are being developed to display complex, preorganized surfaces for binding proteins and to create enzyme-like active sites. In this work, we demonstrate the convergent synthetic approach to this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Just as cyclization is known to stabilize folded peptide conformations, [20][21][22][23][24] so have similar strategies been successful at achieving pre-organized spiroligomer 25 and peptoid macrocycles. [26][27][28][29][30][31][32][33][34] Indeed, preorganization due to cyclization helps explain the prevalence of cyclic designs in the modest corpus of peptoid crystal structures that have been solved to date.…”
Section: Introductionmentioning
confidence: 99%
“…Just as cyclization is known to stabilize folded peptide conformations, [20][21][22][23][24] so have similar strategies been successful at achieving pre-organized spiroligomer 25 and peptoid macrocycles. [26][27][28][29][30][31][32][33][34] Indeed, preorganization due to cyclization helps explain the prevalence of cyclic designs in the modest corpus of peptoid crystal structures that have been solved to date.…”
Section: Introductionmentioning
confidence: 99%
“…This is important as all possible configurations of stereocenters have been used previously. 10,11,16,17,19 On top of that, this strategy of hydantoin alkylation can be applied to a spiroligomer dimer, as shown in Scheme 2 (for a more detailed scheme showing a complete structure of 33 and synthesis of 32, please see Scheme SI-1 on page 121 of the Supporting Information.) We synthesized a spiroligomer dimer to which we applied one of our alkylation methods.…”
Section: The Journal Of Organic Chemistrymentioning
confidence: 99%
“…We have successfully attached alkyl, allyl, and benzyl halides to both the imide and amide position of the hydantoin. The application of this alkylation method to the synthesis of spirocyclic ring systems allows the utilization of these highly diverse bifunctionalized 4-hydantoin-proline derivatives as small molecules or as the termini of larger spiroligomer structures . Herein, we detail the synthesis of nine of the numerous potential variants of these substituted 4-hydantoin-proline derivatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Just as cyclization is known to stabilize folded peptide conformations, so have similar strategies been successful at achieving preorganized spiroligomer and peptoid macrocycles. Indeed, preorganization due to cyclization helps explain the prevalence of cyclic designs in the modest corpus of peptoid crystal structures that have been solved to date . Interestingly, it has been found that cyclic peptoids can host metal cation adducts through the coordination of backbone carbonyl groups, , reminiscent of natural products such as mycotoxins …”
Section: Introductionmentioning
confidence: 99%